Legal Protection of Children as Perpetrators & Victims of Bullying (Analysis of Restorative Justice Application for Minors in North Sumatra Police) - Nasution, Abdul Halim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This article is entitled Legal Protection of Children as Perpetrators and Victims of Bullying (Analysis of the Application of Restorative Justice for Minors in the North Sumatra Regional Police). Bullying is a serious problem that has a negative impact on the development of children, both as perpetrators and victims. Legal protection of children in the context of bullying is essential to ensure their rights are protected and to prevent long-term adverse impacts. This research aims to examine the legal protection provided to children as perpetrators and victims of bullying in Indonesia according to the Child Protection Law. The problem formulation of this research: 1. How is the process of criminal bullying of minors in its application in North Sumatra olda? 2. How is the application of the Law on criminal acts of bullying minors according to Law No. 11 of 2012 concerning the Child Criminal Justice System? 3. How is the legal protection of children as perpetrators and victims of bulling effectively implemented? The methodology used is qualitative research involving literature review and analysis of legal documents, including Law No. 35 of 2014 concerning Child Protection, as well as other relevant regulations and policies. In addition, in-depth interviews were conducted with various relevant parties, including law enforcement, educators and child protection experts. The data were thematically analyzed to identify key patterns in the legal protection of children related to bullying.The results showed that the Child Protection Law has provided a strong legal basis to protect children from bullying, both as perpetrators and victims. However, implementation and law enforcement still need to be improved. A holistic approach involving various parties, including families, schools and the government, is needed to create a safe and supportive environment for children. This research recommends increasing legal awareness, training for law enforcers, as well as strengthening the role of educational institutions in preventing and handling bullying.